A Method for Verifying the Behavioral Consistency between Public Business Process and Private Business Process Based on Environment. Issue 4 (February 2020) - Chen, Yitong
Abstract: The cross-organizational business process is characterized by privacy, collaboration, autonomy, dynamic interaction structure, etc. It is necessary to model and analyze the cross-organizational business process in order to ensure the accuracy and consistency of process interaction among different organizations. The open workflow net proposed on the basis of Petri net is used as a tool to model the cross-organizational business process. The cross-organizational business process is divided into two parts, namely private process and public process. The private process is regarded as the internal view of the organization, and the public process is regarded as the external view of the interaction between an organization and other organizations. The interaction behavior of model verification is regarded as the starting point with regard to the behavioral consistency problem of the model. A method for verifying the behavioral consistency based on environment is proposed, which is more relaxed than the existing method for verifying the behavioral consistency based on mutual simulation and more consistent with the asynchronous communication among organizations.